2022
DOI: 10.3390/su142215359
|View full text |Cite
|
Sign up to set email alerts
|

An Experiential Learning-Based Virtual Reality Approach to Foster Students’ Vocabulary Acquisition and Learning Engagement in English for Geography

Abstract: EFL learners encounter a number of challenges in English for specific purposes, especially in understanding and remembering vocabulary. Therefore, exploring effective ways to improve their vocabulary and its applications is the key area of ESP. VR, as a newer type of audiovisual input on incidental vocabulary learning, is an important tool for innovation in language education. With its sense of presence and immersion, VR constructs an experiential learning process for students involving incidental vocabulary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 53 publications
(68 reference statements)
2
8
0
Order By: Relevance
“…The explanation for this result, nonetheless, presumably lies in the fact that the term "innovative teaching" is not often used in studies using virtual reality in education. For, in fact, there is an upward trend in the publication of studies on virtual reality, as evidenced by the many high-quality papers devoted to the effectiveness of virtual reality in enhancing student engagement (Li et al, 2022;Riner et al, 2022;Y. Song et al, 2023), motivation (H.-L. Chen & Liao, 2022;Liu et al, 2022;Ozdemir & Ozturk, 2022), and learning outcomes (Banjo-Ogunnowo & Chisholm, 2022;C.-H. Chen et al, 2021;Yamaguchi et al, 2022) recently published in credible journals.…”
Section: Discussionmentioning
confidence: 99%
“…The explanation for this result, nonetheless, presumably lies in the fact that the term "innovative teaching" is not often used in studies using virtual reality in education. For, in fact, there is an upward trend in the publication of studies on virtual reality, as evidenced by the many high-quality papers devoted to the effectiveness of virtual reality in enhancing student engagement (Li et al, 2022;Riner et al, 2022;Y. Song et al, 2023), motivation (H.-L. Chen & Liao, 2022;Liu et al, 2022;Ozdemir & Ozturk, 2022), and learning outcomes (Banjo-Ogunnowo & Chisholm, 2022;C.-H. Chen et al, 2021;Yamaguchi et al, 2022) recently published in credible journals.…”
Section: Discussionmentioning
confidence: 99%
“…Devotion to society that has been carried out, carried out with method lecture, method practicum and evaluation in accordance with need from participant activity training and assurance that the participants can understand and can build augmented reality applications for free. Method lecture used as an approach in delivery appropriate teaching materials to participant training (Oswald et al, 2019;Li et al, 2022). Basically, use method lectures only can be done For as opener from activity training as well as explain material base to the participants still training lay to topic or theme from augmented reality training.…”
Section: Methodsmentioning
confidence: 99%
“…(Chirobocea-Tudor, 2018). Consistently, Li, Ying, Chen & Guan (2022) examined the use of virtual reality (VR) as an innovative means for improving incidental vocabulary learning and promoting students' learning engagement and performance. The findings demonstrated that the experiential learning-based VR was effective and enjoyable, and led to enhancing geography students' incidental vocabulary acquisition and engagement.…”
Section: Vocabularymentioning
confidence: 99%